2008
DOI: 10.1598/rt.61.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Differences Between Reading Skills and Reading Strategies

Abstract: The terms reading skill and reading strategy are central to how we conceptualize and teach reading. Despite their importance and widespread use, the terms are not consistently used or understood. This article examines the current and historical uses of the terms, defines them, and describes their differences, similarities, and relationships. Implications for teaching reading skills and strategies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
304
0
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(357 citation statements)
references
References 14 publications
1
304
0
26
Order By: Relevance
“…18). It has also been suggested that strategies play a more important role in the early stages of reading development (Skaftun, 2011) or when decoding or comprehension proves difficult to the reader even at the later stages of development (Afflerbach, Pearson, & Paris, 2008). Against this background, our study also serves the purpose of determining whether DSI has a differential impact on secondary students with varying reading ability.…”
Section: Introductionmentioning
confidence: 89%
“…18). It has also been suggested that strategies play a more important role in the early stages of reading development (Skaftun, 2011) or when decoding or comprehension proves difficult to the reader even at the later stages of development (Afflerbach, Pearson, & Paris, 2008). Against this background, our study also serves the purpose of determining whether DSI has a differential impact on secondary students with varying reading ability.…”
Section: Introductionmentioning
confidence: 89%
“…Theoretically, researchers have successfully characterized strategies as deep, surface, motivated, cognitive, or metacognitive with some degree of validity and reliability. But in empirical practice, how is one to determine whether the intentionality, effortfulness, or volition associated with strategies-in contrast to habituated and cognitively effortless nature of skills-is manifested (Afflerbach, Pearson, & Paris, 2008;Harris, Alexander, & Graham, 2008)? Certainly relying on self-report measures cannot illuminate those differences in compelling or convincing ways.…”
Section: Constructs and The Search For Conceptual Claritymentioning
confidence: 99%
“…A repertoire of 13 reading strategies was selected for this training through reviewing the related literature (Afflerbach, Pearson, & Paris, 2008;Baker & Brown, 1984;Baumann et al, 1993;Grabe, 2009;Jiang & Grabe, 2007;Nuttall, 1996). The list of these strategies is attached in the Appendix.…”
Section: Reading Strategy Training Using Think-aloud Proceduresmentioning
confidence: 99%